Parents of preterm children narrate constructive aspects of their experiences. Issue 21 (20th June 2019) - Widding, Ulrika; Hägglöf, Bruno; Farooqi, Aijaz
Abstract: Aims and objectives: To explore how parents of preterm infants express the constructive aspects of their experiences. Using the notion of post‐traumatic growth as a back‐drop, this study supplements the research on parents' difficulties by providing a more nuanced understanding of what it is like to have a preterm child. Background: Researchers have reported that parents feel afraid, worried, helpless, powerless, guilty and stressed, as well as that preterm birth can be associated with physical and psychological ill health among parents; however, a few researchers have found indications of post‐traumatic growth among parents. Design: This study includes qualitative interviews and relates to COREQ guidelines for reporting qualitative research. Methods: A total of 13 mothers and 10 fathers of extremely preterm children, as well as 11 mothers and 7 fathers of moderately preterm children, were interviewed. The data analysis was based on thematic analysis. Results: The analysis resulted in six themes that describe various constructive aspects of having a preterm child: acceptance of the fact that events do not always occur as planned; gratitude and reconsideration of the situation; reappraisal of close relationships; reliance on one's own ability to deal with events; thankfulness for what one has; and openness to being exposed to various kinds of people and their experiences. Conclusions: The parents recounted constructive aspects of their experiences such as an altered understanding of themselves, others and life itself. These themes provide a more nuanced way of understanding how parents can relate to having preterm children. Relevance to clinical practice: This knowledge can help professionals to enable parents to activate their social network and to acknowledge their care for each other, as well as to help parents see beyond cultural ideals regarding childbirth and family life and to find their own solutions to everyday life.